Comparative Analysis of Wedding Ceremonies in Uzbek and Korakalpok Folklore (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article presents a comparative analysis of wedding rituals in Uzbek and Karakalpak folklore and their artistic interpretations. In this process, actions and words are spoken. The modern appearance of these rituals is also described.